2020
DOI: 10.3389/fpsyg.2020.00009
|View full text |Cite
|
Sign up to set email alerts
|

An Application of the Social Cognitive Career Theory Model of Career Self-Management to College Athletes’ Career Planning for Life After Sport

Abstract: Drawing on Lent and Brown (2013) recently developed Social Cognitive Career Theory (SCCT) model of Career Self-Management (CSM), we aimed to determine the key predictors and underlying theoretical mechanisms of college athletes' career planning processes for life after sport. Ten variables were operationalized (i.e., career planning for life after sport, career decision self-efficacy, career goals, perceived career planning support from coaches, perceived career planning barriers, conscientiousness, openness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 73 publications
(157 reference statements)
1
41
0
1
Order By: Relevance
“…However, researches on career maturity, adaptability, and / or future expectations of professional esports athletes have not been found in the literature. On the other hand, in the literature review, various researches were found in sports and educational sciences, especially on sportsman career planning and management (Sandstedt et al, 2004;Lavallee, 2006;Tyrance, Harris & Post, 2013;Kocadağ, 2017;Ribeiro & Rima, 2019, Wendling et al, 2020. From this point of view, studies investigating career planning and future expectations of esports athletes are very few (Taylor, 2012;Seo, 2016;Salo, 2017;Anderson et al, 2018;Johnson & Woodstock, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, researches on career maturity, adaptability, and / or future expectations of professional esports athletes have not been found in the literature. On the other hand, in the literature review, various researches were found in sports and educational sciences, especially on sportsman career planning and management (Sandstedt et al, 2004;Lavallee, 2006;Tyrance, Harris & Post, 2013;Kocadağ, 2017;Ribeiro & Rima, 2019, Wendling et al, 2020. From this point of view, studies investigating career planning and future expectations of esports athletes are very few (Taylor, 2012;Seo, 2016;Salo, 2017;Anderson et al, 2018;Johnson & Woodstock, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literatürde fiziksel spor disiplinlerindeki sporcuların kariyer yönetimi ve kariyer beklentilerine ilişkin çeşitli çalışmalar bulunmaktadır (Sandstedt et al, 2004;Lavallee, 2006;Tyrance, Harris & Post, 2013;Kocadağ, 2017;Ribeiro & Rima, 2019, Wendling et al, 2020. Ancak profesyonel espor oyuncularına dönük kariyer planlaması, yönetimi ve/veya gelecek beklentilerine dönük araştırmalar literatürde oldukça azdır (Salo, 2017;Andersen et al, 2018;Johnson & Woodstock, 2019…”
Section: Literatür öZetiunclassified
“…In this regard, it is reasonable to assume that definitions of self-efficacy and goals are proximal antecedents of career planning (Demulier et al, 2013). Besides the theoretical point of view among the variables, several empirical studies have been shown the associations among selfefficacy, career goals, and career planning (e.g., Wendling and Sagas, 2020), which reinforces the importance of these variables in career transitions.…”
Section: Introductionmentioning
confidence: 99%
“…To flatten the curve of coronavirus disease 2019 (COVID-19) pandemic, many governments around the world have implemented unprecedentedly strict preventive measures, such as prolonged school closures and home confinement [ 1 , 2 ]. Although necessary to limit the spread of the virus, responses to the COVID-19 emergency have led to incomparable and precipitous changes in human behavior [ 3 ].…”
Section: Introductionmentioning
confidence: 99%